Japón en 2024: el sismo de Noto, el escándalo kick-backs y los cambios económicos y geopolíticos - Álvarez Pérez, Alfredo (El Colegio de México A.C., 2025)
This issue attempts to summarize some of the most important events in Japanese public life between September 2023 and October 2024. The disasters on the Noto Peninsula and the alarm over the prediction of the “Great South Sea Trench Earthquake”. The difficulties faced by the Liberal Democratic Party and Fumio Kishida in his last year as prime minister; in particular, the biggest corruption scandal since the 1990s and its electoral repercussions. Inflation that led the Bank of Japan to return to positive interest rates, making the symbolic end of Abenomics. The perception and responses of the Japanese government to the changes, threats and opportunities it sees in the international arena.